2016
DOI: 10.3233/ch-151968
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the neutrophil to lymphocyte ratio in young subjects with acute myocardial infarction

Abstract: Abstract. In the last years the neutrophil to lymphocyte ratio (NLR) has been examined in cardiovascular disorders and in particular in coronary artery disease and acute myocardial infarction (AMI). Now we examined this parameter in subjects with juvenile myocardial infarction at the initial stage and after 3 and 12 months. We enrolled 123 young subjects (112 men and 11 women, mean age 39.4 ± 5.8 yrs) with AMI. The time interval between the AMI onset and the investigation was 13 ± 7 days. The mean value of NLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…Among 7 studies of ACS outcome, 2 studies [ 28 , 32 ] reported OR of high versus low NLR, 2 studies [ 30 , 31 ] reported mean differences between ACS patients and controls, and 3 studies [ 18 , 27 , 29 ] reported both.…”
Section: Resultsmentioning
confidence: 99%
“…Among 7 studies of ACS outcome, 2 studies [ 28 , 32 ] reported OR of high versus low NLR, 2 studies [ 30 , 31 ] reported mean differences between ACS patients and controls, and 3 studies [ 18 , 27 , 29 ] reported both.…”
Section: Resultsmentioning
confidence: 99%
“…We found that decreasing NLR was associated with the disease progression, which was not congruent with previous studies. In one systematic review and meta-analysis, including thirtyeight article, high NLR was significantly associated with the risks of coronary artery disease, acute coronary syndrome, stroke and combined cardiovascular events 33 ; however, at the initial stage of the disease, NLR did not correlated with the cardiovascular determinants 34 . In Nordestgaard et al 35 study neutrophil and NLR were not significant determinants for Myocardial Infarction in the seemingly healthy population.…”
Section: Or (Ci 95%) P-value or (Ci 95%) P-value Or (Ci 95%) P-value mentioning
confidence: 99%
“…Previously, we have separately examined these parameters in the same population of patients with JMI. 23,24 This article is a part of the scientific project identified as ‘Sicilian study on juvenile myocardial infarction’. Myocardial infarction occurring at a relatively young age (45 years is the age limit generally accepted) has peculiarities in the pattern of risk factors and coronary lesions, which can justify its definition as a separate clinical condition.…”
Section: Introductionmentioning
confidence: 99%